Praktik Terbaik dalam Budidaya Kelapa Sawit untuk Petani Kecil: Studi Kasus di Kabupaten Lamandau - Anggara, Yoga; Kusdarjito, Cungki; Kadarso (JURNAL AGRICA, 2025)
The palm oil industry in Indonesia has become one of the largest sources of vegetable oil in the world and is important to the country's economy, contributing significantly to state revenue. This study aims to analyze the socioeconomic characteristics of smallholder oil palm farmers in Lamandau Regency, as well as the challenges they face in cultivation practices. The method used is a qualitative approach through literature study and semi-structured interviews with two smallholder farmers. The results of the study show that the majority of smallholders have less than 10 hectares of land and are classified as lower-middle income. They are generally not members of cooperatives or farmer associations, which results in weak bargaining power in the supply chain and dependence on middlemen for the sale of their crops. In addition, smallholder farmers face challenges in accessing financing, inadequate infrastructure, and market price fluctuations. The conclusion of this study shows that in order to improve the welfare of smallholder farmers and palm oil productivity, efforts are needed to increase access to financing, strengthen farmer organizations through cooperatives, and improve infrastructure and access to better markets.